Centring settler colonialism in rural Australian multicultures: race, place and local identities. Issue 9 (4th July 2021) - Butler, Rose; Ben, Jehonathan
ABSTRACT: In the current age of rural mobilities and economic restructuring, the ethnic and racial compositions of rural towns across Anglosphere nations of the Global North have significantly transformed. As a result of these changes, the conditions which support rural multicultures are increasingly relevant to scholarship and policy-making. 'Everyday multiculturalism' and 'convivialities' have become key approaches within such research in rural environments. These perspectives offer important insights into understanding complex social relationships, reciprocities and circumstances of belonging in rural places. However, as UK-based critiques argue, a focus on 'everyday multiculturalism' and 'convivialities' may also risk obscuring how colonial legacies have shaped and informed racialised and classed hierarchies of belonging in distinct contexts. In this paper we turn these critiques to settler colonial Australia and its increasingly diverse rural towns. We bring together emerging literature in the study of rural migration with scholarship from Indigenous studies and anthropology on Aboriginal and non-Aboriginal rural social relations. Working at the intersection of these bodies of works, we argue that the histories and structures of settler colonialism be centred in research on rural multicultures, as these legacies and ongoing conditions shape social relationships in contemporary rural Australia.